2022
DOI: 10.1016/j.ygyno.2022.01.006
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro study of the potential hazards of surgical smoke during cervical cancer treatment with an ultrasonic scalpel

Abstract: Malignant cells were not observed in surgical smoke from cervical cancer treated with ultrasonic scalpel.• HPV were found in surgical smoke, which was capable of transmitting infection to HPV negative cervical cancer cells.• Surgical smoke inhibited cell proliferation of SAEC and THP1 cells, which may show cytotoxicity to respiratory system.• Some volatile organic compounds were found in surgical smoke, which exceeded the standard of indoor air quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Yan et al (2022) studied the chemical contents of surgical smoke collected during laparoscopic hysterectomy in 11 human cervical cancer patients. Bipolar electrocoagulation was also used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yan et al (2022) studied the chemical contents of surgical smoke collected during laparoscopic hysterectomy in 11 human cervical cancer patients. Bipolar electrocoagulation was also used.…”
Section: Resultsmentioning
confidence: 99%
“…Yan et al (2022) performed ultrasonic scalpel instrumentation of tumours induced in 24 mice with four human cervical cancer cells. Three cell lines were human papillomavirus (HPV) positive and one negative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV-DNA has been proven to be distinctly isolatable from the surgical fumes produced during these treatments, indicating that healthcare professionals are passively exposed to HPVs during procedures to treat afflicted patients by particles found in the ambient air. 2 , 10 Moreover, it has been found that the viral particles containing HPV-DNAisolated from the surgical fumes are capable of infecting HPV-negative cervical cancer cell lines. 10 It becomes then imperative that healthcare providers in positions vulnerable to exposure to such surgical fumes, and thus HPV-DNA molecules, mitigate their risk of susceptibility to becoming infected by a type of HPV.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 10 Moreover, it has been found that the viral particles containing HPV-DNAisolated from the surgical fumes are capable of infecting HPV-negative cervical cancer cell lines. 10 It becomes then imperative that healthcare providers in positions vulnerable to exposure to such surgical fumes, and thus HPV-DNA molecules, mitigate their risk of susceptibility to becoming infected by a type of HPV. 2 , 11 …”
Section: Introductionmentioning
confidence: 99%